Communication: Preparing undergraduate radiation therapy students for initial clinical patient interactions. Issue 4 (November 2019) - Kelly, T.; Surjan, Y.; Rinks, M.; Beech, J.; Warren-Forward, H.M.
Abstract: Introduction: Radiation therapy students need to demonstrate appropriate communication skills when entering the clinical environment. To assist students with preparation for their first clinical placement a clinical reasoning module comprising theory and practical sessions was developed. This paper describes the module and presents the results of student evaluations. Methods: The module consisted of lectures, observational role-play and participatory role-play. Students were ultimately tasked with providing information to a simulated patient (SP). Each student received feedback independently from the SP, peers and facilitator. At the conclusion of the module, students had the opportunity to provide feedback via an anonymous survey (8 Likert scale questions with space for written comment). Data was analysed both quantitatively and qualitatively. Results: Four hundred and thirty seven students were enrolled in the course between 2008 and 2016 and the response rate of the survey was 93%. Even though most students reported some level of anxiety before and during the role-play sessions, the majority of students perceived all aspects of the module to be extremely/very useful. The most useful aspect of the module (Likert scale assessment) was the feedback provided by the SP. The two most important themes arising from the thematic analysis were gaining an understanding of the role of the radiation therapist and the complexities of patient interactions. Conclusion: Overall, the module was deemed successful with students becoming conscious of newly acquired clinical knowledge whilst acknowledging patient feelings during interactions. Collaborative critiquing contributed to students' ability to self-reflect to improve clinical interactions. Highlights: Module developed to prepare radiation therapy students for clinical placement. A mix of teaching mechanisms appeared to appeal to student learning styles. Students learnt the radiation therapist role while concurrently educating patients. Students enjoyed receiving feedback from three different perspectives.